2021
DOI: 10.18521/ktd.757819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Online Anatomy Education Given in Medicine and Dentistry Faculties of Universities During Covid-19 Pandemic with Student Feedback

Abstract: We are experiencing the effects of Covid-19 pandemic as the whole world. All educational facilities have been negatively affected within this period. In this study, the aim was to evaluate online Anatomy education during Covid-19 pandemic with students' feedbacks and it was questioned whether it would be efficient to use online education more actively in the following years. Methods: A total of 1127 first and second year students from Dentistry Faculty and Medicine Faculty of Düzce, Karabük and İnönü Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Researchers reported findings consistent with and inconsistent with our study on medical school students with similar socio-demographic and academic characteristics [ 20 , 30 , 32 ]. Students’ opinions such as distance anatomy education save students time and students are more active in learning have been identified as similar views revealed in our questionnaire.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Researchers reported findings consistent with and inconsistent with our study on medical school students with similar socio-demographic and academic characteristics [ 20 , 30 , 32 ]. Students’ opinions such as distance anatomy education save students time and students are more active in learning have been identified as similar views revealed in our questionnaire.…”
Section: Discussioncontrasting
confidence: 86%
“…Some studies and case reports on medical students’ views on distance anatomy education in our country and worldwide have been published [ 22 ]. In some studies conducted in our country, it was determined that medical students were worried about not being physically present in the laboratory environment and they felt the lack of face-to-face theoretical anatomy education [ 20 , 30 , 32 ]. These results were found to be similar to our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in many studies in the literature, students reported that the efficiency they received from online lectures was less than face-to-face education (12,15). In addition, students stated that they wanted to continue face-to-face education especially for practical courses after the pandemic and that distance education can only be considered as a complement to traditional education methods (11,15,18). In studies conducted in Germany and Turkey, the majority of both, students and educators, reported that they preferred the hybrid education model in which distance education continues to a certain extent in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Covid-19 pandemic has adversely affected every field of life all over the world; but the largest impact was seen in the field of education (11). With the beginning of the pandemic, almost all faculties have been start to distance education instead of face-to-face training.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, 30.4% of the dentistry students who voluntarily participated in the study and 28.6% of the medical faculty students gave feedback as follows: "If I had the chance to choose, I would prefer distance anatomy education". To the question: "I think that anatomy theoretical lessons should be taught online when the pandemic is over", 33.9% of the volunteers of the dental faculty of dentistry and 36% of the participants who are the medical faculty students, strongly disagree [26].…”
Section: Discussionmentioning
confidence: 99%